PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA PT ASTRA INTERNASIONAL TBK PERIODE 2013-2022 - Wardi, Muhamad; Puji Astuti, Eni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of liquidity (QR) and leverage (DAR) on profitability (NPM) at PT Astra International Tbk for the 2013-2022 period, both partially and simultaneously. The research method used is quantitative, using secondary data obtained from the Company's Financial Reports. For data analysis used are classic assumption tests, statistical tests which include regression tests, hypothesis tests and coefficient of determination. The research results show that partially Liquidity (QR) has a negative and insignificant effect on Profitability (NPM) with the hypothesis test results obtained tcount > ttable or -2.227 > ttable 2.365 and a significance value of 0.061 > 0.05. Partially Leverage (DAR) has a negative and significant effect on Profitability (NPM) with the hypothesis test results obtained tcount > ttable or -2.376 > 2.365 and with a significance value of 0.049 < 0.05. Simultaneously Liquidity (QR) and Leverage (DAR) have no effect on Profitability (NPM) with the hypothesis test results obtained Fcount > Ftable or 2,898 < 4.46 and a significance value of 0.121 > 0.05. The coefficient of determination value is 29.7%, this shows that Profitability (NPM) can be explained or there is a contribution from Liquidity (QR) and Leverage (DAR).